Communicating Corrected Risk Assessments and Uncertainty About COVID-19 in the Post-truth Era - Fernandes, Adalberto (Frontiers in Communication, 2021)
The COVID-19 pandemic has been a challenge for Science Communication in terms of addressing the question of uncertainty and how it translates into risk. This task has been aggravated by the complexity of the pandemic and the current post-truth environment. We argue that there is a need to analyze the practices of correcting risk information that is uncertain, but not necessarily false, made by online news media about COVID-19. This is a point of analysis where the uncertainty and risk linked to science, the pandemic, and the post-truth condition meet. Our qualitative discursive analysis yielded three important results: 1) uncertainty can be fought by increasing uncertainty; 2) a multiplication of facts or reasons may not be the most prominent strategy in practices of correction; 3) the use of hyperlinks with additional information can increase uncertainty and risk.